2013
DOI: 10.1371/journal.pone.0053648
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Monoclonal Antibody to Human Laminin α5 Chain Strongly Inhibits Integrin-Mediated Cell Adhesion and Migration on Laminins 511 and 521

Abstract: Laminins, a large family of αβγ heterotrimeric proteins mainly found in basement membranes, are strong promoters of adhesion and migration of multiple cell types, such as tumor and immune cells, via several integrin receptors. Among laminin α (LMα) chains, α5 displays the widest tissue distribution in adult life and is synthesized by most cell types. Here, we have generated and characterized five novel monoclonal antibodies (mAbs) to the human LMα5 chain to further study the biological relevance of α5 laminins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
(112 reference statements)
3
14
0
Order By: Relevance
“…Expression of laminin‐332 is induced at the wounded edge of epidermis and at the leading edge of invading carcinomas. Additionally, laminin‐332 and ‐511 enhance migration and scattering of the cells through binding to integrin α3β1, and blockade of these interactions by mAb strongly inhibited α3β1 integrin‐mediated adhesion of cancer cells . In the present study, ITGA3 was shown to be associated with invasion of phospho‐ERK‐positive cells (Figs a,f).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Expression of laminin‐332 is induced at the wounded edge of epidermis and at the leading edge of invading carcinomas. Additionally, laminin‐332 and ‐511 enhance migration and scattering of the cells through binding to integrin α3β1, and blockade of these interactions by mAb strongly inhibited α3β1 integrin‐mediated adhesion of cancer cells . In the present study, ITGA3 was shown to be associated with invasion of phospho‐ERK‐positive cells (Figs a,f).…”
Section: Discussionsupporting
confidence: 58%
“…Cancer cell invasion was recently classified into two categories, so‐called “collective cancer cell invasion” and “fibroblast‐led collective invasion” . In the former, cancer cells invade without the assistance of other cells, whereas the latter highlights the importance of certain fibroblasts that initiate a collective invasion chain of cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…Mouse monoclonal antibodies (mAbs) to human laminin α4 (clones 3H2 and 6C3) and α5 (clones 4B5 and 4B12) chains are described in our previous studies . Laminin β1 and β2 chains were detected with mAbs DG10 and C4, respectively .…”
Section: Methodsmentioning
confidence: 98%
“…In a recent report, five antibodies were developed which recognized the LMa5 chain (Wondimu et al, 2013). Those antibodies were useful for immunohistochemistry; however, one of the antibodies (8G9) inhibited integrin-dependent adhesion and migration of several cancer lines on LM-511.…”
Section: Inhibition Studiesmentioning
confidence: 99%
“…Used in series, antibodies that recognize individual chains of LM-511 could be employed to specifically purify LM-511 from complex tissues such as human placenta. A recent report described a LMa5 specific monoclonal antibody (mAb) 8G9, with a specificity different to mAb 4C7, which is capable of inhibiting LM-511-dependent cell adhesion and migration of several cancer cell types (Wondimu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%